Upaya Kesehatan Masyarakat dalam Konteks Covid 19 - Annisa Nurida (PROCEEDING UMSURABAYA, 2020)
AbstractPrevention efforts are more efficient, do not cost a lot of for care, do not cause pain and do notlose productive time. Public Health Science as a science that prioritizes handling on preventionefforts. Preventive medicine is intended to prevent disease from occurring, prevent diseasefrom progressing to more severe level and prevent disease complications and cause disability.A disease incidence is affected by three factors, called as epidemiologic triangle, in which itconsists of host, agent and environment. If a disease occurs in a person or a population, whatshould be conducted is to strengthen at least one of the three elements of the epidemiologictriangle.Herd Immunity has shifted in meaning now, where it is similar to the process of allowing peopleor populations to be naturally exposed to Covid-19. In fact, the concept of herd immunity isbest applied when a population has been vaccinated. With this shift in understanding, it isundeniable that the number of deaths in Indonesia has increased.Public Health Science is a multidisciplinary field. It is a science and art that maintains andimproves public health through community organizing. Public health is very broad not onlyfrom sanitation engineering, curative medicine, preventive medicine and even social science,it is all related to economic stability in a region and even a country.Keywords: preventive medicine, epidemiologic triangle, herd immunity